Analytical and functional similarity of biosimilar ABP 798 with rituximab reference product. (November 2020) - Seo, Neungseon; Huang, Zhe; Kuhns, Scott; Sweet, Heather; Cao, Shawn; Wikström, Mats; Liu, Jennifer
Abstract: ABP 798 is a biosimilar candidate to rituximab reference product (RP). This comprehensive analytical similarity assessment was designed to assess the structural and functional similarity of ABP 798, rituximab (US), and rituximab (EU) using sensitive state-of-the-art analytical techniques capable of detecting small differences in product attributes. The similarity assessment was performed to evaluate product quality attributes associated with Fab, Fab/Fc, and Fc domains, including those known to affect the mechanisms of action. ABP 798 has the same amino acid sequence and exhibits similar secondary and tertiary structures, similar glycan and post-translational modification profiles, and biological activities as rituximab RP. There are minor differences in biochemical attributes, which are not considered clinically meaningful. The results of the analytical and functional similarity assessment demonstrate that ABP 798 is highly analytically similar to rituximab RP. These results support the totality of evidence and the scientific justification for extrapolation of ABP 798 to all therapeutic indications approved for rituximab.